Developing Physics SSP Based on the Problem Solving to Improve the Process Skills and Problem-Solving Ability - Mujib Ubaidillah; Insih Wilujeng (Journal of Science Education Research, 2019)
The research aimed to1) find out the expedience of physics Subject-Specific Pedagogy (SSP) based on the problem solving, and 2) improve the science process skills and problem-solving ability of grade X students of SMA N 7 Yogyakarta in electricity subject using the physics SSP based on the problem-solving. The particular research was a research and development using the 4-D development model consisting of 1) define, 2) design, 3) development, and 4) dissemination. The developed SSP was tested in a limited and extensive field trial. The sample of the limited field trial was 15 students, while in the extensive field trial consisted of 30 students in the control class and 29 students in the experimental class. The statistical analysis used multivariate analysis. The results were 1) The developed SSP, in terms of the syllabus, Lesson Plan, and worksheet, was in the excellent category, while the science process skills instrument test, problem-solving instrument test, and the textbook were in a good category, 2) The implementation of SSP for physics learning based on a problem solving had significant effect on improving the students science process skills and problem solving ability. The result of the multivariate test showed a significantly different effect between students that learn using the physics SSP based on the problem solving and students learn using the physics SSP based on the conventional model.